Gageure : lettre d'information du GAGE. (Paris : GAGE, 1989)
Fonds Suzan Daniel (FSD)
Periodiciteit : maandelijksRedactie : c/o Librairie Les Mots à la Bouche, 6 rue Sainte-Croix de la Bretonnerie, 75004 Paris
Frans
Periodiek